Microstructure and Density Characterization for Nano and Micro Alumina-Aluminum Composites Produced by Powder Metallurgy Process - Abed, Abdulrahman Najim; Sabri, Ban Ali (Al-Nahrain Journal for Engineering Sciences, 2017)
Al2O3 is a major reinforcement in aluminum-based composites, which have been developing rapidly in recent years. The aim of this paper is to investigate the effect of alumina phases and amounts on the physical properties of fabricated Al-Al2O3 composite. Alpha micro and gamma nano of alumina with particle size of 30µm and 20 nm respectively reinforced aluminum matrix of 45 µm. The percentage of reinforcement material were in the range of (5, 10 and 15wt.%) fabricated by powder metallurgy technique. Specimens dimensions were a disc specimens with 11mm diameter and 5 mm thickness. The green density was achieved under compaction pressure of 500MPa, and then sintered under pressure less sintering at 500ºC in a vacuumed tube furnace for two hours Physical properties of the composite samples have been studied such as relative density, sintered density, porosity, microstructure characteristics, particles distribution, agglomeration, grain sizes and  granularity accumulation distribution. It has been noticed that at the micro alumina phase, its relative densities are decreased when there is an increase in amount of micro alumina addition, on the contrary in case of nano composites, where the relative density are increasing along with the increase in nano alumina addition. At micro and nano composites, the produced relative densities are less than the pure aluminum relative density. Agglomeration are increasing with the increase in amount of reinforcement, while its more obvious with nano composite. Grain size reduced with the increase in amount of alumina in micro and nano composites, while, the obtained average grain size diameter is less in nano composite than in micro composites. It is obvious from the results that the variation in physical properties and microstructure of Al-Al2O3 composite are depends on both of alumina phases (size) and percentages. At 15wt.% of nano alumina higher relative density and lower porosity will be obtained.